Symptomatic Lymphocele After Kidney Transplantation: a Single-Center Experience - Zargar-Shoshtari, Mohammad Ali; Soleimani, Mohammadjavad; Salimi, Hormoz; Mehravaran, Kaveh (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: In a retrospective study, we evaluated the frequency, clinical presentation, and management of lymphocele in kidney transplant recipients operated on in a single center. Materials and Methods: Between September 1984 and June 2005, we had 2147 kidney transplantations from living donors. During the follow-up period, ultrasonography was performed in symptomatic patients and those with elevated serum creatinine level postoperatively. Other radiological procedures were done in complicated cases. Patients with lymphocele were treated by percutaneous drainage with or without injection of sclerotizing agent (povidone iodine). If recurrence occurred, surgical intraperitoneal drainage was performed. In cases with multiloculated collection or inappropriate access for percutaneous drainage, the primary approach was surgical intraperitoneal drainage. Results: Symptomatic lymphocele collection was seen in 17 kidney recipients of our series (0.8%; 95% confidence interval, 0.4% to 1.2%). It presented with elevation of serum creatinine concentrations (47.1%), pain and abdominopelvic swelling (29.4%), and lower extremity edema (23.5%). Percutaneous drainage was used for the treatment of lymphocele in 11 patients, but recurrence occurred in 7 (63.6%). These cases were treated with open surgical drainage. In 6 patients, the primary approach was surgical intraperitoneal drainage, because of multiloculated collection or inappropriate access for percutaneous drainage. All of the patients were treated successfully and no graft loss occurred during the follow-up period. Conclusion: Symptomatic lymphocele is an uncommon complication after kidney transplantation. Surgical intraperitoneal drainage is the most effective approach for the management of symptomatic lymphocele.